Industrial training report: Fujiaire Global Sdn Bhd. Special project: Determinants of efficiency: evidence from Japan Exchange - Zulkifli, Farah Yasmin (Universiti Teknologi MARA, Perlis, 2024)
Embarking on my memorable and enlightening 6-month industrial training at Fujiaire Global Sdn. Bhd. was truly transformative. My experience with Fujiaire Global Sdn. Bhd. revealed significant benefits of working with the company, including exposure to cutting-edge technology and practices in the HVAC industry. The company's commitment to innovation and sustainability provided a platform for practical learning and professional growth This executive summary provides an overview of our comprehensive research on efficiency dynamics in various industries, with a focus on the oil and gas sector. The study aimed to enhance understanding by expanding the sample size and updating the dataset to include recent years' data, thus ensuring relevance across evolving market conditions. Key findings highlight the importance of random sampling methods in ensuring statistical reliability and industry applicability. Incorporating broader economic indicators and regulatory influences further enriched our analysis, shedding light on efficiency dynamics within different sectors. Our research underscores the significance of these findings for stakeholders across industries, offering actionable insights to optimize efficiency strategies amidst dynamic market environments.